Familial restrictive cardiomyopathy with atrioventricular block and skeletal myopathy. Issue 2 (February 1990) - Fitzpatrick, A P; Shapiro, L M; Rickards, A F; Poole-Wilson, P A
Abstract : Five generations of an Italian family with an autosomal dominant restrictive cardiomyopathy are described. Members of four generations were examined. Symptoms usually developed in the third or fourth decade but the disease did occur in childhood. Initially the condition was characterised by normal ventricular size and systolic function with increased diastolic filling pressures in both ventricles and consequent bi-atrial enlargement. Cardiac catheterisation showed a left ventricular filling pattern of "dip and plateau". The electrocardiogram typically showed non-specific changes in the ST segment and T wave and changes indicating considerable atrial enlargement, which were confirmed by echocardiography. Light microscopy of two endocardial biopsy specimens showed no specific features but excluded the endomyocardial fibrosis of eosinophilic heart disease, amyloid, and specific heart muscle diseases. At necropsy in one case examined under light microscopy extensive patchy fibrosis was found throughout the endocardium, myocardium, and subepicardium, but there were no features typical of eosinophilic heart disease. Histopathological and biochemical examination of skeletal muscle identified no abnormality. The disease often had an insidious course over five to ten years after presentation. Bundle branch blocks, leading to complete atrioventricular block, however, often occurred and may be the first manifestation. Some individuals who survived into the fifth decade developed a progressive, non-wasting skeletal myopathy.